AKTIVITAS GURU DALAM PEMBELAJARAN MENGGUNAKAN INKUIRI TERBIMBING PADA MATERI EKOSISTEM DI KELAS X-“E MAN 2 MODEL BANJARMASIN - Ulimaz, Almira (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2018)
Based on the results of preliminary observations in MAN 2 Model Banjarmasin in the X-E class of the midterm test, there were 52% of students who had not yet reached the School Minimum Completion Criteria (KKM), where the KKM in this school was 75. The researcher chose this school as the object of research because generally learning is still teacher-centered, so students become less active in the process of teaching and learning activities (KBM), and learning has never been carried out using guided inquiry. To maximize teaching and learning activities that will impact on the increase in students learning outcomes which are expected to be above the KKM, teacher activities should be improved first. Therefore this research was carried out which aims to increase the activity of teachers in learning using guided inquiry in ecosystem material. This study is a Classroom Action Research (CAR) designed in 2 learning cycles, where each cycle consists of 2 meetings. The research subjects were students of class X-E MAN 2 Model Banjarmasin academic year2013/2014. The techniques of collecting data used were observation and questionnaire. The data obtained were analyzed qualitatively and quantitatively. The results of the study show that teacher activities can be improved by using a guided inquiry learning model.